Selection for mefloquine resistance in Plasmodium falciparum is linked to amplification of the pfmdr1 gene and cross-resistance to halofantrine and quinine. - Cowman, A F (1994)
Two chloroquine-resistant cloned isolates of Plasmodium falciparum were subjected to mefloquine selection to test if this resulted in alterations in chloroquine sensitivity and amplification of the pfmdr1 gene. The mefloquine-resistant lines derived by this selection were shown to have amplified and overexpressed the pfmdr1 gene and its protein product (Pgh1). Macrorestriction maps of chromosome 5, where pfmdr1 is encoded, showed that this chromosome has increased in size in response to mefloquine selection, indicating the presence of a gene(s) in this area of the genome that confers a selective advantage in the presence of mefloquine. Concomitant with the increase in mefloquine resistance was a corresponding increase in the level of resistance to halofantrine and quinine, suggesting a true multidrug-resistance phenotype. The mefloquine-selected parasite lines also showed an inverse relationship between the level of chloroquine resistance and increased pfmdr1 gene copy number. These results have important implications for the derivation of amplified copies of the pfmdr1 gene in field isolates, as they suggest that quinine pressure may be involved.